2021
DOI: 10.1021/acsmedchemlett.1c00196
|View full text |Cite
|
Sign up to set email alerts
|

Dual Glycolate Oxidase/Lactate Dehydrogenase A Inhibitors for Primary Hyperoxaluria

Abstract: Both glycolate oxidase (GO) and lactate dehydrogenase A (LDHA) influence the endogenous synthesis of oxalate and are clinically validated targets for treatment of primary hyperoxaluria (PH). We investigated whether dual inhibition of GO and LDHA may provide advantage over single agents in treating PH. Utilizing a structure-based drug design (SBDD) approach, we developed a series of novel, potent, dual GO/LDHA inhibitors. X-ray crystal structures of compound 15 bound to individual GO and LDHA proteins validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…As molecules are not static, this compound will likely form HBs with these two residues during GO inhibition emphasizing the importance of performing molecular dynamic studies after the docking analysis. Therefore, HBs with FMN, Tyr26, and Arg263 are also essential for GO inhibition agreeing with the literature 64 , 65 . As the studied compounds are bigger than Gl, other essential interactions can be found in structure size.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As molecules are not static, this compound will likely form HBs with these two residues during GO inhibition emphasizing the importance of performing molecular dynamic studies after the docking analysis. Therefore, HBs with FMN, Tyr26, and Arg263 are also essential for GO inhibition agreeing with the literature 64 , 65 . As the studied compounds are bigger than Gl, other essential interactions can be found in structure size.…”
Section: Resultssupporting
confidence: 92%
“…Occupancies demonstrate that the amino acids spotted to be important during the docking studies are crucial to forming strong interactions. The most essential amino acids are Tyr26, Arg167, and Arg263 being in concordance with the literature 64 , 65 . Arg167 presents the highest occupancies being present in 6 of the 10 compounds.…”
Section: Resultssupporting
confidence: 90%
“…To contextualize the active site fragments, we first analyzed the binding modes of known HAO1 inhibitors, by comparing a 1.2 Å resolution structure of hHAO1 bound with 5-[(4-methylphenyl)sulfanyl]-1,2,3-thiadiazole-4-carboxylic acid (CCPST) determined in this study (PDB code 6gmc; Supplementary Table S2 and Figure S4 ), with reported structures of triazole, dioxo-pyrroline, benzoic acid, and indazole carboxylic acid inhibitors bound to either spinach glycolate oxidase (sGOX; PDB codes 1al7 and 1al8; Stenberg and Lindqvist, 1997 ) or hHAO1 ( Supplementary Figure S5 ; PDB codes 2rdt ( Murray et al, 2008 ), 2w0u ( Bourhis et al, 2009 ), 6w44, 6w45, 6w4c ( Lee et al, 2021 ) and 7m2o ( Ding et al, 2021 )), sGOX-FMN-glyoxylate (PDB code 1gox; Lindqvist, 1989 ) and hHAO1-FMN-glycolate (PDB codes 2nzl ( Mackinnon et al, 2018 ) and 6gmb, determined in this study). These inhibitor-bound structures all demonstrate similar features: displacement of residues lining the substrate-binding pocket (Tyr26, Trp110, Tyr132, Arg167, Arg263) relative to glycolate/glyoxylate-bound hHAO1 structures, interaction with residues involved in substrate turnover (Asp160, Lys236, His260), and disruption of the hydrogen bonding network posited to maintain gating loop conformation during catalysis (Trp110, Tyr134, Leu191, Tyr208; ( Murray et al, 2008 )) ( Supplementary Table S3 and Figure S5 ).…”
Section: Resultsmentioning
confidence: 60%
“…Of the seven compounds that could occupy the gating loop pocket ( Supplementary Figure S6 ), only one does so. This compound was reported as a dual lactate dehydrogenase (LDH)-HAO1 inhibitor (5-[(5'-{1-(4-carboxy-1,3-thiazol-2-yl)-5-(cyclopropylmethyl)-4-[(3-fluoro-4-sulfamoylphenyl)methyl]-1H-pyrazol-3-yl}-2′-fluoro [1,1′-biphenyl]-4-yl)oxy]-1H-1,2,3-triazole-4-carboxylic acid; PDB code 7m2o ( Ding et al, 2021 )), and the group occupying this pocket is the thiazole-carboxylic acid component of the LDH-targeting moiety ( Supplementary Figure S6C ).…”
Section: Resultsmentioning
confidence: 99%
“…If both RNAi medications fail singularly, combined administration of GO and LDHA blockers may be considered. Examples are the PH1 infant treated with lumasiran and stiripentol [ 85 ] (a small molecule that inhibits LDHA, see below) (Table 1 ), and new small molecules that inhibit both GO and LDHA enzymes, showing efficacy in primary hepatocytes from all PH animal models (1–3) [ 96 , 97 ]. If these all fail, patients must remain on standard treatment of care and a close follow-up evaluation of the disease course.…”
Section: Current Treatment Optionsmentioning
confidence: 99%